Mechanical and biodegradation properties of fresh and rotten jicama starches based bioplastics - Nazree, Anne Aleesa; Adrus, Nadia; Ab Muis, Zarina; Hashim, Haslenda; Baharulrazi, Norfhairna; Che Man, Siti Hajjar; Zainal Alam, Muhd Nazrul Hisham; A. Majid, Rohah; Johnson, Edwina; Abdullah, Abdul Razak; Chuprat, Bahrul Razha; Ali, Fathilah; et al. (Wiley, 2022)
Recently, starch-based bioplastics have been proposed to curb the problem caused by conventional plastics. Yet, current bioplastics are made from food sources which cause competition with food industries. Hence, we have produced bioplastics using rotten starch-based material to tackle this problem. In this study, a comprehensive investigation has been carried out on the preparation of bioplastics extracted from fresh jicama (FJ) and rotten jicama (RJ). Specifically, glycerol as the plasticizer and starch contents were varied to obtain bioplastic with the optimum properties via tensile, chemical and thermal characterizations. The results have confirmed that both FJ and RJ starch bioplastics possessed similar characteristics in terms of physical appearance, transparency and chemical functionalities. Moreover, the tensile and thermal properties of RJ and FJ bioplastics fall within the range specification for packaging applications. FJ bioplastic has maximum stress of 0.43 MPa and maximum strain of 50 MPa at an optimized concentration (St31%_gly6.75) which tells that they formed stronger and higher flexibility than RJ bioplastics. Importantly, the RJ bioplastics have a faster biodegradation rate compared to FJ bioplastics. In conclusion, bioplastics from rotten starch have properties as good as FJ and served as a feasible platform for the development of bioplastics from rotten sources.